Transjejunal endoscopic ultrasound‐guided pancreatic drainage for pancreatic jejunostomy stricture using a forward‐viewing echoendoscope in a patient with altered anatomy. Issue 1 (1st April 2022) - Shimizu, Hiroshi; Suzuki, Rei; Sato, Yuki; Takagi, Tadayuki; Abe, Naoto; Irie, Hiroki; Sugimoto, Mitsuru; Yanagita, Takumi; Kobashi, Ryoichiro; Hashimoto, Minami; Kato, Tsunetaka; Takasumi, Mika; et al.
ABSTRACT: Pancreatic jejunostomy stricture (PJS) is one of the major late complications after pancreaticoduodenectomy. Endoscopic ultrasound‐guided pancreatic drainage (EUS‐PD) is considered a salvage treatment for symptomatic PJS after endoscopic retrograde pancreatography failure; however, the technical success rate of the endoscopic treatment of PJS remains unsatisfactory, mainly due to surgically altered anatomy. Herein, we describe a case of PJS successfully treated with transjejunal EUS‐PD using a forward‐viewing echoendoscope. A 62‐year‐old man who suffered from repetitive severe back pain due to PJS was referred to our hospital. Since transgastric EUS‐PD was difficult, we attempted transjejunal EUS‐PD using a forward‐viewing echoendoscope. To facilitate scope insertion, we first straightened the afferent jejunal loop and placed a stiff guidewire. With this scheme, we successfully performed transjejunal EUS‐PD and placed a 5‐Fr plastic stent. In conclusion, this technique is useful for treating patients with PJS when transgastric EUS‐PD is difficult.